1981
DOI: 10.1128/aem.41.4.950-955.1981
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cecal bacteria of normal pigs

Abstract: One hundred ninety-two isolates from cecal contents of three normal weaned pigs were obtained by means of anaerobic roll tube methods and were characterized. Seventy-eight percent of the isolates were gram-negative. The most numerous species isolated from each of the pigs was Bacteroides ruminicola. This species accounted for 35% of the isolates that were characterized, and Selenomonas ruminantium accounted for 21% of the isolates. Other gram-negative bacteria isolated from all three pigs were Butyrivibrio fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 26 publications
1
44
1
1
Order By: Relevance
“…The genera Mitsuokella has also been reported in the gastrointestinal tract of the pig (Mitsuoka et al 1974;Leser et al 2002), with the species M. multiacidus being the dominant within the genera (Leser et al 2002). Robinson et al (1981) identified 2% of the bacterial isolates from the caecal contents of pigs as being Bacteroides multiacidus, the genera later changed to Mitsuokella (Stewart et al 1997). On the basis of their 16S rDNA sequences S. ruminantium and M. multiacidus cluster closely (Paster et al 1995;Leser et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…The genera Mitsuokella has also been reported in the gastrointestinal tract of the pig (Mitsuoka et al 1974;Leser et al 2002), with the species M. multiacidus being the dominant within the genera (Leser et al 2002). Robinson et al (1981) identified 2% of the bacterial isolates from the caecal contents of pigs as being Bacteroides multiacidus, the genera later changed to Mitsuokella (Stewart et al 1997). On the basis of their 16S rDNA sequences S. ruminantium and M. multiacidus cluster closely (Paster et al 1995;Leser et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…The majority of bacteria in the large intestine are obligate anaerobes, since the lumen in the large intestine is under an anaerobic condition. In pigs, the following genera are the predominant bacteria: Lactobacillus , Enterococcus , Ruminococcus , Clostridium , Eubacterium , Fusobacterium , Bacteroides , Prevotella , Selenomonus , Veillonella , Megasphaera , Peptostreptococcus , Acidaminococcus , Butyrivibrio , Lachnospira , and Escherichia (Robinson et al. 1981, 1984; Moore, Moore et al.…”
Section: Role Of Intestinal Microfloramentioning
confidence: 99%
“…The gut microbial ecosystem in mammals is highly complex, typically comprising more than 400-500 species and viable counts of up to 10 12 per gram of gut content in the large intestine (Moore et al, 1974;Eckburg et al, 2005). Several studies have investigated the species diversity of the pig intestine through phenotypic analysis of isolates obtained by anaerobic culturing (Tannock et al, 1970;Salanitro et al, 1977;Robinson et al, 1981;Varel et al, 1987). Culturing, however, is likely to recover some bacteria more readily than others, and is laborious (Zoetendal et al, 2004).…”
Section: Introductionmentioning
confidence: 99%